Torque Dynamic Coordinated Control for HEV based on the ISG Motor Torque Compensation - Deng Tao; Lu Renzhi; Li Yanan; Lin Chunsong (Jixie chuandong)
For the fluctuations problem of driveline torque which results from working-mode switching of dual-clutch parallel hybrid electric vehicles with integrated starter / Generator（ ISG）,focusing on study the process of transferring from pure electric working model to only engine working model.Based on the method of optimal the total efficiency of hybrid electric vehicle,the steady-state energy management control strategy is established,and then steady torque distribution area is achieved,which is the basis of coordination and control of dynamic torque.For the problem adopted the engine dynamic torque estimate genetic algorithm based on BP neural network algorithm,and ISG motor torque compensation method is proposed for dynamic torque coordinated control strategy.The simulation results show that the method proposed above can significantly decreases the torque fluctuations of working model transferring process,at the same time,the jerk to driveline is greatly reduced.